DETEKTOR JARAK DENGAN SENSOR ULTRASONIK BERBASIS MIKROKONTROLER - Prawiroredjo, Kiki; Asteria, Nyssa (Jurnal Teknik Elektro, 2008)
A Distance Detector is a circuit that is built using ultrasonic sensor to detect objects aroundone`s car and AT89S52 microcontroller as the processor. An Ultrasonic sensor will detectobjects around the car. The sensorâs transmitter will transmit ultrasonic waves. If theultrasonic waves bounce back to the receiver, it means that there is an object around the car.Microcontroller will count the time needed to receive the ultrasonic waves and determine thedistance between the object and the car. The distance can be read from the Liquid CrystalDisplay (LCD) or Light Emitting Diode (LED) panel that is placed in front of the car driver.After being assembled and tested, this device works properly. This device can detect anobject up to the distance of 2 meters from the sensor. The deviation between the real distanceand the calculated one ranges from 0.82% to 34.40%. the longer the distance, the smallerthe deviation.Keywords: ultrasonic sensor, microcontroller, distance, LCD, LED